Temperaturas de armazenamento e uso de soluções de manutenção na pós-colheita de gérberas vermelhas - Muniz, Ana Carolina Corrêa [UNESP] (2015)
Most of the gerberas presents very short postharvest life, mainly due to the stem bending caused in most cases, by the blockage of the xylem vessels by microorganisms. Many conservation techniques have been employed in an attempt to maintain the quality and extend the life of these flowers, such as: storage at low temperature and the use of maintenance solution with antimicrobial compounds, with or without carbohydrates. In this context, this study aimed to use low storage temperatures and preservatives added to maintenance solution to extend the postharvest life of cut gerberas cv. Intenza. In the first experiment, the inflorescences, kept in distilled water, were stored at the temperatures of 22 ºC (control); 12 ºC; 8 ºC and 4 ºC. In the second experiment the inflorescences remained in maintenance solutions containing: distilled water (control); 10 μL L-1 of carvacrol; 25 μL L-1 of carvacrol; 50 μL L-1 of carvacrol, keeping them in ambient conditions (22±2 ºC; 65±4% relative humidity). In the third experiment, the stems were placed in the maintenance solutions: distilled water (control); 25 μL L-1 of carvacrol + 4% of sucrose; 25 μL L-1 of carvacrol + 6% of sucrose; 50 μL L-1 of carvacrol + 4% of sucrose; 50 μL L-1 of carvacrol + 6% of sucrose, and stored at 22±2 ºC; 65±4% relative humidity. In the fourth experiment, the gerberas were submitted to the following maintenance solutions: distilled water (control); Sumaveg® 0.33 mg L-1; Sumaveg® 0.66 mg L-1; Sumaveg® 0.33 mg L-1 + 6% of sucrose; Sumaveg® 0.66 mg L-1 + 6% of sucrose and kept at 22±2 ºC; 65±4% relative humidity. The experiments were conducted in a completely randomized design with split plot with three replications and three inflorescences per repetition. Every three days were evaluated the variation of the fresh mass of the inflorescences, and color, relative water content, soluble and reducer sugars content and total carotenoids content of ...